Review of Thoracis Trauma at Shree Birendra Hospital Chhauni, Kathmandu, Nepal - Rajbhandari, G L (Medical Journal of Shree Birendra Hospital, 2006)
Review of Thoracis Trauma at Shree Birendra Hospital Chhauni, Kathmandu, Nepal